DEVELOPMENT OF A CAD TOOL FOR DESIGNER GARMENTS - Shalini Singh (International Journal of Research Science and Management, 2017)
According to Cooklin, Pattern making is an art. It is the art of manipulating and shaping a flat piece of fabric to confirm to one or more curves of the human figure. Pattern making is a bridge function between design and production. A sketch can be turned into a garment via a pattern which interprets the design in the form of the garment components[1]. This study aims to develop a pattern draft for designer garment through CAD software as well as through C++ programming. The pattern made in tools available in industry is compared and analyzed with the developed tool. Designer dress used in apparel industry has been designed analyzed and compared. This study provides an insight for development in 2D virtual fit simulation technology for effective prototyping and quality assessment in the fashion industry..